2014
DOI: 10.1039/c4ja00069b
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of arsenic in rice grains using ICP-MS and fs LA-ICP-MS

Abstract: With rice being the main staple crop in Asian countries such as China, Korea and Japan, the detection of arsenic (As), an element known to be carcinogenic to humans, has been the topic of high public interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…The mapping of the biologically essential trace metals (i.e., Cu, Zn, Fe), metalloids (i.e., Se), or non-metals (i.e., S, P, I) is of increasing interest in modern bio-analytics (Becker et al, 2010 ). LA-ICP-MS and SIMS are two major MSI ion sources of choice for trace elements localization (Heard et al, 2002 ; Zhu et al, 2012 ; Choi et al, 2014 ; Hanć et al, 2014 ). In particular, the absence of charging-up effects combined with fewer matrix effects makes LA-ICP-MS a simple quantification tool in which is possible to apply certified standard reference materials or matrix-matched laboratory standards (Becker et al, 2010 ).…”
Section: Application Of Msi In Plantsmentioning
confidence: 99%
“…The mapping of the biologically essential trace metals (i.e., Cu, Zn, Fe), metalloids (i.e., Se), or non-metals (i.e., S, P, I) is of increasing interest in modern bio-analytics (Becker et al, 2010 ). LA-ICP-MS and SIMS are two major MSI ion sources of choice for trace elements localization (Heard et al, 2002 ; Zhu et al, 2012 ; Choi et al, 2014 ; Hanć et al, 2014 ). In particular, the absence of charging-up effects combined with fewer matrix effects makes LA-ICP-MS a simple quantification tool in which is possible to apply certified standard reference materials or matrix-matched laboratory standards (Becker et al, 2010 ).…”
Section: Application Of Msi In Plantsmentioning
confidence: 99%
“…The differences among the samples are considered to be because the As content of rice is influenced by the environment. Choi et al (2014) reported the iAs content of rice varies greatly depending on the cultivation country, region, variety, and harvest time. Differences in As content according to regions seem to be related to regional variations, such as the soil background, irrigation water, and agricultural process, rather than the genotypic difference (Naito et al, 2015).…”
Section: Exposure Assessment Of Ias In Products Of Bran Powder and Tamentioning
confidence: 99%
“…Other studies have found that As concentration can depend on harvesting time as well as with increasing milling ratios ( Choi et al, 2014 ), factors also differ by region and country and their milling process. These major factors can account for differences observed between regions and cultivars.…”
Section: Resultsmentioning
confidence: 95%